2016
DOI: 10.1111/jvp.12295
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of a 10‐day course of ibuprofen inHolstein calves

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) are recommended for various conditions in cattle. Ibuprofen is an inexpensive short-acting NSAID and is readily available in liquid formulation for administration to bottle-fed calves. We compared the adverse effects of a 10-day course of ibuprofen and placebo in 16 five- to six-week-old Holstein bull calves that were being treated for experimentally induced bovine respiratory syncytial virus infection. Ibuprofen was administered as a liquid in milk replacer at 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…[18][19][20] Although rarely used in agriculture, where long-acting parenteral agents are preferred, 10-day courses of oral ibuprofen appear reasonably well-tolerated in pre-ruminant calves, although abomasal ulcers and interstitial nephritis have been reported. [21] We have previously shown improved clinical score but also increased viral shedding in bovine calves when ibuprofen rather than placebo was initiated on the day following experimental bovine RSV infection. [22] GS-561937 FPI initiated on the day following inoculation both improved clinical scores and decreased viral shedding; a smaller benefit was seen when this FPI was started three days after infection.…”
Section: Introductionmentioning
confidence: 97%
“…[18][19][20] Although rarely used in agriculture, where long-acting parenteral agents are preferred, 10-day courses of oral ibuprofen appear reasonably well-tolerated in pre-ruminant calves, although abomasal ulcers and interstitial nephritis have been reported. [21] We have previously shown improved clinical score but also increased viral shedding in bovine calves when ibuprofen rather than placebo was initiated on the day following experimental bovine RSV infection. [22] GS-561937 FPI initiated on the day following inoculation both improved clinical scores and decreased viral shedding; a smaller benefit was seen when this FPI was started three days after infection.…”
Section: Introductionmentioning
confidence: 97%
“…Ibuprofen is short acting and has limited safety data in bovines. [ 63 ] The proof of concept design also limits its applicability to pediatrics, but ibuprofen is a widely used NSAID in pediatrics at the dosage we used. The safety of ibuprofen is well established in children.…”
Section: Discussionmentioning
confidence: 99%
“…Most NSAID are likely given as part of the treatment for respiratory diseases, similar to AM drugs (Pardon et al, 2012b). Ibuprofen (Walsh et al, 2016) and other NSAID (Semrad and Dubielzig, 1994;Sasaki et al, 2012) have been found to cause abomasal lesions in calves. Additionally, NSAID are a known cause of peptic ulcers in humans (Yeomans and Naesdal, 2008).…”
Section: Medicationmentioning
confidence: 99%